Measurement of the cross section for prompt isolated diphoton production in pp̄ collisions at √s=1.96TeV - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
This Letter reports a measurement of the cross section of prompt isolated photon pair production in pp̄ collisions at a total energy √s=1.96TeV using data of 5.36fb-1 integrated luminosity collected with the CDF II detector at the Fermilab Tevatron. The measured cross section, differential in basic kinematic variables, is compared with three perturbative QCD predictions, a leading order parton shower calculation and two next-to-leading order calculations. The next-to-leading order calculations reproduce most aspects of the data. By including photon radiation from quarks before and after hard scattering, the parton shower prediction becomes competitive with the next-to-leading order predictions.